Land Resource Cards: An Innovative Approach to Empower Farmers for Site-Specific Farm Resource Management - Ravi, K. N.; Patil, S. L.; Biswas, Hrittick; Ramesha, M. N.; Naik, B. S.; Ojasvi, P. R.; Dupdal, Ravi; Prabhavathi, M.; Kumar, Suresh; Morade, A. S. (Indian Journal of Extension Education, 2021)
The paper investigates an innovative extension approach of generation and distribution of Land Resource Cards, developed from Land Resource Inventory database, used for site-specific farm resource management in watersheds adopted under World Bank funded Sujala-III project. Extent of reach, satisfaction level and training status of Land Resource Cards in 12 model micro-watersheds located in different agro-climatic regions of Karnataka with a sample size of 720 farmers was assessed. The Land Resource Cards reached only 18 per cent of farmers while 22 per cent of farmers were trained for its utilization. However, 77 per cent were satisfied with the information provided and 23 per cent suggested for further improvement in cards for greater utility. The overall farmer’s perception on capacity building on land resource cards revealed that they were very useful in farm-level resource management. Hence, need for replication of similar approach in all database driven watersheds to be implemented in the future with adoption of modifications is suggested.
Keywords: LRI database; Extension approach; Farmer perception; Land resource cards; Sujala-III project